Vrikshayurved Plantation Techniques: A Review - Abnave Prajkta Dilip,; Avalaskar Amit D, (International Journal of Ayurveda and Pharma Research, 2021)
Use of chemicals for plant growth and its management has led to soil and water pollution. It has ultimately affected the quality of medicinal plants.  In the other hand Vrikshayurved (science of plant life) have fully organic and time tested methods to deal with entire plant life. It mostly emphasizes on the selection of land, seed collection, seed treatment, different plant propagation methods, irrigation, manure, plant protection, plant disease management, crop harvesting and storage of produce. Thus, Vrikshayurved encompasses both agriculture and forestry.Materials and method- Collection and compilation of useful information has been done from concerned articles and texts of Ayurved and Vrikshayurved texts such as Surpala’s Vrikshayurved, Upavan Vinod, Varahamihir’s Brihat Samhita, Charak Samhita and Sushruta Samhita.Discussion and Conclusion- This article represents concise information of Vrikshayurved plantation techniques for seed propagation, grafting, stem propagation, tuber propagation and plant transplantation. All these methods are affordable, natural, and chemical free. All substances used by Vrikshayurved methodology have its Ayurvedic significance. Thus, Vrikshayurved and Manushya Ayurved are interdependent. Use of Vrikshayurved in modern agriculture and forestry can result in better agriculture system and sustainable forestry. Hence formation of standard guidelines for Vrikshayurved methodologies through research work is mandatory for better tomorrow.